Bilingualism and the Monumental Landscape in the Triodos of Ephesos - Gatzke, Andrea F. (Anabasis. Studia Classica et Orientalia, 2018)
This paper concerns the bilingual monuments in the city center of Roman Ephesos, an area often called ‘Triodos’ because of the three intersecting roads there. The author argues that the concentration of bilingualism in this part of the city reveals its deeper nature as a cultural center. Further, the author explains how the bilingual inscriptions affected the linguistic landscape of Ephesos, suggesting that these monuments were built to target traffic from certain parts of the city.